Chronic Periodontal Disease May Influence the Pulp Sensitivity Response: Clinical Evaluation in Consecutive Patients. (5th April 2012) - Zuza, Elizangela Partata; Vanzato Carrareto, Ana Luiza; Pontes, Ana Emília Farias; Brunozzi, Marcelo; Pires, Juliana Rico; Toledo, Benedicto Egbert Corrêa
Abstract : Purpose . The aim of the present study was to evaluate the clinical response of the pulp in teeth with chronic periodontitis. Methods . Consecutive patients who had been admitted to the Clinics of Periodontology and fulfilled the criteria of inclusion were enrolled from January to December 2007. Ninety-eight single-root teeth from 27 patients with chronic periodontitis were evaluated clinically with regard to clinical attachment level (CAL), probing depth (PD), and gingival recession (REC). After periodontal measurements, Pulpal Sensitivity (PS) was evaluated with the use of a cooling stimulus test. Data was analyzed with Student's t test and contingency C coefficient. Results . Teeth that responded positively to PS test presented lower values of CAL (7.8 ± 2.8 mm), PD (5.0 ± 2.3 mm), and REC (2.8 ± 1.8 mm) in comparison to those that responded negatively (CAL = 12.0 ± 2.2 mm; PD = 7.9 ± 1.6 mm; REC = 4.1 ± 2.4 mm) (P < 0.01, Student's t test). In addition, significant correlations were observed between PS and periodontal parameters. Conclusions . Within the limits of this study, it could be suggested that the progression of periodontitis may significantly influence the negative pulpal response.